#### Question

Solve the following quadratic equations by factorization:

6x^{2} - x - 2 = 0

#### Solution

We have

6x^{2} - x - 2 = 0

6x^{2} + 3x - 4x - 2 = 0

3x(2x + 1) - 2(2x + 1) = 0

(3x - 2)(2x + 1) = 0

either 3x - 2 = 0 or 2x + 1 = 0

3x = 2 or 2x = -1

x = 2/3 or x = -1/2

Thus, x = 2/3 and x = -1/2 are two roots of the equation 6x^{2} - x - 2 = 0

Is there an error in this question or solution?

Solution Solve the Following Quadratic Equations by Factorization: 6x2 - X - 2 = 0 Concept: Solutions of Quadratic Equations by Factorization.